1989
DOI: 10.1007/bf00285334
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of insulin and oral antidiabetic agents on glucose and energy metabolism in Type 2 (non-insulin-dependent) diabetes mellitus

Abstract: Which therapy should be used in Type 2 (non-insulin-dependent) diabetic patients with "secondary sulfonylurea failure", insulin or a combination of sulfonylurea and metformin? To address this question, we have compared the effect of 6 months of insulin therapy twice daily with that of a combination of glibenclamide and metformin in 24 Type 2 diabetic subjects, who no longer responded to treatment with sulfonylureas. Both treatments resulted in an equivalent 30% improvement in mean daily blood glucose (p less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
47
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 30 publications
(36 reference statements)
8
47
1
1
Order By: Relevance
“…The components of this increased BWt have not been clearly defined; some studies have shown equal increases in fat and FFM [6], whereas others indicated the increase as predominantly FFM [5]. These discrepancies could result from differences in study populations (obese vs non-obese), insulin regimens (conventional vs intensive; continuous vs bolus) or the body composition methodology used (BIA [7][8][9], DXA [5,6] or tritiated water dilution [10]). In contrast, use of the 4-CM [13] in this clinical study provided accurately assessed characterisation of the composition of BWt increases in a group of type 2 diabetes patients from the start of insulin therapy, along with a number of other clinically relevant indices (Table 1), and assessment of BWt distribution through the complementary use of DXA estimates of segmental composition [17,19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The components of this increased BWt have not been clearly defined; some studies have shown equal increases in fat and FFM [6], whereas others indicated the increase as predominantly FFM [5]. These discrepancies could result from differences in study populations (obese vs non-obese), insulin regimens (conventional vs intensive; continuous vs bolus) or the body composition methodology used (BIA [7][8][9], DXA [5,6] or tritiated water dilution [10]). In contrast, use of the 4-CM [13] in this clinical study provided accurately assessed characterisation of the composition of BWt increases in a group of type 2 diabetes patients from the start of insulin therapy, along with a number of other clinically relevant indices (Table 1), and assessment of BWt distribution through the complementary use of DXA estimates of segmental composition [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…This differential body fat distribution could account for the beneficial effects of metformin in patients on insulin therapy [10,14,28,29]. Furthermore, patients who are losing significant BWt prior to insulin therapy may be more likely to gain BWt than those who are not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is commonly observed that treatment of type 2 diabetic patients with sulfonylureas [8][9][10] or insulin [10][11][12] is associated with weight gain. This effect of sulfonylureas and insulin could possibly aggravate the insulin-resistance syndrome associated with type 2 diabetes [2,13,14] and thereby counteract the otherwise beneficial effects of these agents.…”
mentioning
confidence: 99%